AL-ARIYAH, AL-QARDH DAN AL-HIBAH - Novi Indriyani Sitepu (Studia Economica : Jurnal Ekonomi Islam, 2015)
Sometimes, social contract is overlooked in society which in turn can cause problems. 'ariyah is seldom to be discussed in relation to the law, it is showed by the absence of DSN-MUI fatwa, about ariyah and specific discussion in KHES. Qardh that is applied in the banking and other LKS (qard al hasan) can be found  in the DSN-MUI Fatwa and KHES, as well as Grant. Ariyah, qardh and grants are Sunnah for the giver and the permission for the recipient. The social contract, the contract, tabarru’ contract is used all these social contract are allocated properly,  the contribution for infrastructure development will be better.